Traction Man is here! - Grey, Mini. (London : Red Fox, 2006)
Traction Man, a boy's courageous action figure, has a variety of adventures with Scrubbing Brush and other objects in the house.
Five Owls
Notable/Best Books (A.L.A.)
School Library Journal starred
3.2
K-3.
K-3
Keywords: Action figures (Toys) -- Fiction; Brooms and brushes -- Fiction; Toys -- Fiction; Action figures (Toys) -- Fiction; Brooms and brushes -- Fiction; Toys -- Fiction